Multi-modal clustering reveals event-free patient subgroup in colorectal cancer survival - Nikita Janakarajan; Guillaume Larghero; María Rodríguez Martínez (npj Systems Biology and Applications)
Abstract Colorectal cancer (CRC) benefits from a multi-omics-based stratification in the context of survival. Our TCGA-based study employs targeted feature selection and unsupervised clustering to stratify patients based on disease-specific survival, identifying an event-free subgroup undetectable with unimodal data or established consensus molecular subtypes. An analysis of variance and gene set enrichment coupled with clinical characterisation of the clusters reveal findings that support multi-omics-driven precision medicine in CRC.